Understanding how balancing autonomy and power might occur in leading organizational change. Issue 2 (April 2017) - Espedal, Bjarne
Abstract: Leading organizational change involves many leadership skills. The literature indicates that there is one basic underlying skill: the ability to form and use judgment that is informed by analysis and experience. The literature also indicates that constructing and implementing good judgment from analysis and experience requires discretion in terms of autonomy and power . However, the findings from a field study of leaders with strong reputations as change agents demonstrated that it was difficult for change agents to have both autonomy and power. This result introduces critical but underexplored dilemmas associated with balancing autonomy and power in leading change. This article argues that balancing might occur when change agents have learned to understand and handle the dilemmas, and it describes enabling conditions for this learning. Furthermore, a future research agenda is indicated.